National Accounts of Portugal in 2018. Integrated economic accounts, matrix representations and extensions - Santos, Susana (2022)
Starting with the current and accumulation flow accounts, the balance sheets complete the compilation of a sequence of fmancial and non-financial national accounts in its various forms. Within the scope of the central framework of the current version (2008) of the SNA - System of National Accounts, the integrated economic (T-)accounts/tables are thus compiled, as well as possible matrix representations. A high level of aggregation is adopted, and further possibilities of disaggregation are shown or mentioned.Finally, beyond the scope of the central framework, possible extensions are also approached. The concluding remarks, in addition to some methodological aspects, underline the importance of the availability of from-whom-to-whom data to complete matrix representations (especially, national/social accounting matrices) of recognised potential for the study of income and wealth distribution, among other topics